MENGENAL PEREKAYASA EKOSISTEM - Allsay Kitsash Addifisyukha Cintra (Pusat Penelitian Oseanografi LIPI, 2019)
UNDERSTANDING THE ECOSYSTEM ENGINEERS. Ecosystem engineers are organisms that can create, destroy or even maintain the sustainability of a particular habitat. The process of ecosystem engineering begins with structural changes in the environment and subsequently change the abiotic the biotic term or the existence of other organisms. Ecosystem engineers are divided into two, namely autogenic and allogenic engineers. Autogenic engineers change the habitat condition by shifting their body conditions, whereas allogenic engineers that can directly change habitat conditions. The impact of ecosystem engineers on the environment is determined by the magnitude and duration of structural changes made or abandoned by the ecosystem engineer. Understanding the concept of ecosystem engineering is useful as one of the efforts to restore habitat and conservation acts.